The use of orthoses in children with cerebral palsy: Perception of caregivers - Ireno, Janaína Mossini [UNESP]; Chen, Nadia [UNESP]; Zafani, Mariana Dutra [UNESP]; Baleotti, Luciana Ramos [UNESP] (Editora Cubo, 2019)
The orthoses can be used as an adjuvant in the rehabilitation of children with Cerebral Palsy(CP). Studies that investigate caretakers' opinions over the use of the orthoses are fundamental, especially for propositions that aim to produce a positive impact on the use of orthoses by the children. This study's objective was to identify the perception of caretakers of children with CP over the functionality, benefits, and satisfaction over the use of the orthoses. Eighteen caretakers of children with CP, who used upper and/or lower limb orthoses, participated in this study. The data was obtained with questionnaires with open and closed questions. Descriptive and quantitative analysis of the data was made. The results suggest that the satisfaction with the orthoses is linked to the consideration of the caretaker's opinions during the period of prescription and confection of the orthoses; to the guidance provided by professional; to the noticed improvement of the range of movement of fingers and wrists and the increase of the child's balance and confidence while walking. Disconsidering the caretaker's opinions over the orthosis and the perception that the orthoses cause pain or discomfort contributed to the dissatisfaction and/or partial satisfaction of the caretakers. The results of this study may be useful for professionals from many areas of knowledge because they provide a basis to contribute for the efficacy of prescription and intervention by healthcare professionals, as well as elements that may help designers to make orthoses that fulfill the user's expectations and so increase usability, comfort, and satisfaction.
Keywords: Caretaker; Cerebral Palsy; Orthoses; Perception